2019
DOI: 10.24090/maghza.v4i1.2329
|View full text |Cite
|
Sign up to set email alerts
|

Otak dan Akal dalam Ayat-Ayat Neurosains

Abstract: Neuroscience is simply the science that specifically studies Neurons (nerve cells). These nerve cells make up the nervous system, both the central nervous system (brain and spinal cord) and peripheral nerves (31 pairs of spinal nerves and 12 pairs of head nerves). Nerve cells themselves are no longer the smallest unit of nerve cells, the smallest unit of nerve cells (neurons) in synapses, which are the meeting points of two nerve cells that move and forward information (neurotransmitters). At the level of mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…Akal dan otak adalah satu kesatuan yang saling berkaitan. Terdapat keterikatan antara keduanya yang sulit untuk dipisahkan baik kata maupun makna (Noor, 2019). Akal adalah fungsi dari otak sehingga apabila otak seseorang rusak, akalnya pun cacat.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Akal dan otak adalah satu kesatuan yang saling berkaitan. Terdapat keterikatan antara keduanya yang sulit untuk dipisahkan baik kata maupun makna (Noor, 2019). Akal adalah fungsi dari otak sehingga apabila otak seseorang rusak, akalnya pun cacat.…”
Section: Pendahuluanunclassified
“…"Akal" tersebutkan di dalam Al Qur'an sebanyak 49 kali yang seluruhnya dalam bentuk fiil mudhari' (kata kerja yang menunjukkan saat ini atau masa yang akan datang) kecuali satu yang dalam bentuk fiil madhi (kata kerja yang menunjukkan masa lampau). Hal ini menandakan bahwa akal memiliki kedudukan yang tinggi di dalam Al Qur'an (Noor, 2019). Manusia adalah makhluk yang sempurna yang letak kesempurnaan itu ada pada akalnya.…”
Section: Pendahuluanunclassified
“…The brain is the center of good and bad physical conditions. Then the terms "change your brain, change your body" and "change your brain, change your life" were coined (Ahmat Miftakul Huda & Suyadi, 2020;Noor, 2019). Based on this explanation, it can be concluded that functionally, the qalb is very closely related to the function of the mind.…”
Section: Tracing the Traces Of Reason And Brain In Islamic Education ...mentioning
confidence: 99%